Advisory Board (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Assinger, Philipp, AustriaCarr, Deb, Australia     D’Adamo-Weinstein, Lisa, United States   Dolleman, Rusty, United StatesHatch, Meredith, United StatesKang, Dae Joong, South KoreaKlein-Collins, Becky, United StatesLarusdottir, Fjola Maria, Iceland         Nitardy, Charlotte, United StatesRambharose, Rekha, South AfricaWanjiru, Catherine, KenyaWidger, Laura, Ireland